Varieties of hybrid iris of Australian breeding in the CBG of the National Academy of Sciences of Belarus - Borodich Galina Sergeevna (Hortus Botanicus)
Introduction tests of 15 varieties of hybrid iris of modern Australian breeding were carried out on the basis of the iris collection of the Central Botanical Garden of the NAS of Belarus. During the research, the range of Australian irises was studied; their biological features, decorative qualities and economic use were revealed in local conditions. The studied varieties retain their biological, decorative and economic qualities in accordance with varietal characteristics. For the successful growth of Australian irises, it is necessary to follow agronomic techniques for cultivating this crop. Based on the research results, the varieties can be recommended for amateur floriculture.